Tribological Investigation of Bio-Lubricant Based on Madhuca Longifolia and Sesamum Indicum - Sumit Chaudhary, Sonia, Vinod K. Mahto, A. K. Jha, Sahil Verma (International Journal of Advanced Science and Technology, 2020)
The lubricant based on bio-oils or vegetable oil may prove to be an alternative for the conventional lubricant. In this paper, experimental studies of vegetable oil-based bio-lubricants as alternative lubricants have been discussed. The study was conducted to investigate the tribological properties of Mahua oil (Madhuca Longifolia) and Sesame oil (Sesamum Indicum) with blended with 15W40 lubricating oil using four ball tribometer. The bio-lubricant blend was prepared by variable composition of bio-oils in 15W40. The variation in viscosity of the bio-lubricant blend was also measured at different temperatures. The tribological investigation was test was performed at temperature of 75℃ with different loads (196 N and 392 N) following the prescribed ASTM standard where rotating speed was 1200 rpm and test duration of 3600s. The coefficient of friction and wear for different tribological tests were measure. The analysis showed that the blends of Mahua oil and Sesame oil are potential lubricants.